History of Medieaval Hindu India : Volume 3: Downfall of Hindu India - Vaidya, C.V., (Brill | Manohar Publishers & Distributors, 2024)
This book is the last part of the three-volume series of History of Medieaval Hindu India. This book focuses largely on the impact of Hindu Kingdoms with the advent of Turkish invasions in the Indian subcontinent under Mahmud Ghazni. The Mohyal Brahmins, popularly known as Hussaini Brahmins, the rule of Raja Jaipal, the Hindu Shahi kingdom of Kabul, which is the last Hindu kingdom in Afghanistan, and its decline are some of the interesting histories are covered in this book. Raids under the Turkish Sultans at Mathura, Multan, Kangra, Kannauj, Somnath, and Thanesar, and the conquest of Punjab and Kabul under Ghaznavids forms a significant part of the volume. Profiles of the major kingdoms of North and South India like Palas, Gurjara-Pratiharas, Cholas, Gangas, Kakatiyas, Hoysalas, Yadavas, Himalayan kingdoms, and so forth are covered in great detail. The latter part of book covers the ruling elites, the decline of Rajput states, caste stratifications, religious history, and changes in the politics, administration, language, and literature arenas.